Variations of the oxygen minimum zone of the Okhotsk Sea during the last 50 ka as indicated by benthic foraminiferal and biogeochemical data (Izmeneniya zonu kislopodnogo minimuma okhotskogo morya za poslednie 50 tusyach let po bentosnum foraminiferam i biogeokhimikheskim dannum) - Bubenshchikova, N. V.; Nürnberg, Dirk; Gorbarenko, S. A.; Lembke-Jene, Lester (Oceanology, 2010)
Benthic foraminiferal and sediment biogeochemical data (total organic carbon, calcium carbonate and biogenic opal contents) in two cores (1265 and 1312 m water depths) from the southeastern Sakhalin slope and one core (839 m water depth) from the southwestern Kamchatka slope were investigated to reconstruct variations of the oxygen minimum zone during the last 50 ka in the Okhotsk Sea. The oxygen minimum zone was less pronounced during the maximal cooling in the MIS 2 that is suggested to be caused by a maximal expansion of sea ice cover, decrease of marine productivity and increase of production of the oxygenated Okhotsk Sea Intermediate Water (OSIW). A two-step-like strengthening of oxygen minimum zone during the warmings in the Termination Ia and Ib was linked to (1) enhanced oxygen consumption due to degradation of large amount of organic matter in the water column and bottom sediments, originated from increased marine productivity and supply of terrigenous material from the submerged northern shelves; (2) sea ice cover retreat and reduction of OSIW production; (3) freely inflow of the oxygen-depleted deep intermediate water mass from the North Pacific.